Association of post-traumatic acute respiratory distress syndrome on poor prognosis: a single-center study (Journal of the Pakistan Medical Association, 2020)
Objective: To determine the association of post-traumatic acute respiratory distress syndrome (ARDS) on poor prognosis, and provide a theoretical basis for the treatment of patients with post-traumatic ARDS in clinical practice. Methods: This was a retrospective study including trauma victims in the intensive care unit (ICU) of Daping Hospital. The patients were classified as having ARDS or non-ARDS, according to the Berlin definition. Subsequently, these patients were divided into subgroups, according to age, gender and injury site. The relationship between ARDS and prognosis was analyzed, including mechanical ventilation days, length of ICU stay, length of hospital stay, infection, sepsis, multiple organ dysfunction syndrome (MODS) and death. Results: There were 507 trauma patients, out of which 287 cases were with ARDS (56.61%). The duration of mechanical ventilation, ICU stay and hospital stay in the ARDS group was significantly longer than that in the non-ARDS group (5 days vs 3 days, 10 days vs 4 days, 30 days vs 27 days, respectively). In addition, ARDS was associated with an increased risk of infection (P<0.05; OR=4.17; 95%CI=2.72–6.41), sepsis (P<0.05; OR=3.45; 95%CI=2.28–5.22), and MODS (P<0.05; OR=2.82; 95%CI=1.67–4.72), but had no significant association with death (P>0.05). Similar results were found in the subgroup analyses. Conclusions: In conclusion, the prognosis of the patients with post-traumatic ARDS was worse; however, ARDS had little effect on death. Keywords: Trauma; ARDS; Poor Prognosis Continuous...